Kegiatan Bakti Sosial Berbagi Sembako Dalam Rangka Dies Natalis STIE Bima Ke-21 - Nur Khusnul Hamidah; Ismunandar Ismunandar; Muhajirin Muhajirin; Amirulmukminin Amirulmukminin (Jurnal Pemberdayaan: Publikasi Hasil Pengabdian Kepada Masyarakat, 2023)
Social service activities are a form of embodiment of caring attitude, helping each other. This activity reflects a sense of caring, a form of human nature that has sympathy and empathy for people in need, as well as a desire to help alleviate the needs of people's lives, one of which is by distributing groceries. This activity is expected to have a positive effect, especially for underprivileged residents, with the hope that it can help meet the needs of the community, as well as establish friendships between people so that it will build intimacy with the community. This community service activity is fully supported by the entire academic community of the Bima High School of Economics and the lecturers, so that the distribution of food packages can be carried out properly.